2013
DOI: 10.1021/bi400576t
|View full text |Cite
|
Sign up to set email alerts
|

First Three-Dimensional Structure of Toxoplasma gondii Thymidylate Synthase–Dihydrofolate Reductase: Insights for Catalysis, Interdomain Interactions, and Substrate Channeling

Abstract: Most species, such as humans, have monofunctional forms of thymidylate synthase (TS) and dihydrofolate reductase (DHFR) that are key folate metabolism enzymes making critical folate components required for DNA synthesis. In contrast, several parasitic protozoa, including Toxoplasma gondii, contain a unique bifunctional thymidylate synthase-dihydrofolate reductase (TS-DHFR) having the catalytic activities contained on a single polypeptide chain. The prevalence of T. gondii infection across the world, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…1, A and B). Since the x-ray crystal structure of L. major DHFR-TS was determined, additional structures of bifunctional DHFR-TS enzymes from other protozoan species, such as P. falciparum DFHR-TS (8), Cryptosporidium hominis DHFR-TS (10), and Toxoplasma gondii DHFR-TS (11), have also been solved. Interestingly, these bifunctional protozoan enzymes share a common V-shaped geometry, with the main interface between the two monomers located at the bottom of the V shape where the TS domains intersect (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1, A and B). Since the x-ray crystal structure of L. major DHFR-TS was determined, additional structures of bifunctional DHFR-TS enzymes from other protozoan species, such as P. falciparum DFHR-TS (8), Cryptosporidium hominis DHFR-TS (10), and Toxoplasma gondii DHFR-TS (11), have also been solved. Interestingly, these bifunctional protozoan enzymes share a common V-shaped geometry, with the main interface between the two monomers located at the bottom of the V shape where the TS domains intersect (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Dual functionality accelerates metabolic processing via substrate channeling enabled by intradomain cross-talk and allosteric modulation. 4 In contrast, the majority of eukaryotic organisms enlist two distinct enzymes to carry out an identical set of reactions, further exemplifying the parasite's evolutionary advantage toward rapid proliferation. These characteristics make protozoan TS-DHFR an attractive target for pharmacologic intervention.…”
mentioning
confidence: 99%
“…In addition, we have also, for the very first time, solved the X-ray crystal structure of the bifunctional tgTS-DHFR enzyme with compounds 2 and 3 . 16 In cell cuture study, compound 3 showed similar potency to PM, a highly effective standard drug used as a control in these studies. We have thus demonstrated with 2 and 3 that structure variation affords increased selectivity while maintaining potency (compared to 1 ).…”
mentioning
confidence: 78%